Experimental verification of regenerable magnetically modified montmorillonite and its application for heavy metals removal from metallurgical waste leachates. (February 2021) - Tokarčíková, Michaela; Seidlerová, Jana; Motyka, Oldřich; Životský, Ondřej; Drobíková, Klára; Gabor, Roman
Graphical abstract: Highlights: Successful elimination of Zn(II), Cd(II), Pb(II) using MMt from wastewater. The selectivity sequence was determined: Zn(II) > Cd(II) > Pb(II). Less than 0.04 mg/g of Fe leached during the sorption experiment. MMt regenerability > 98 % after fifth adsorption/desorption cycle. Advantages: easy to prepare, fast regenerability, sorption and separation of MMt. Abstract: Using magnetic sorbents to pollutants eliminations seem to be an efficient, easy to apply and low-cost technique. However, the majority of studies focus on the study of sorption properties using model solutions and research on actual wastewater is largely missing. Therefore, this study aims to assess the application of magnetically modified montmorillonite (MMt) to eliminate Zn(II), Cd(II) and Pb(II) cations from metallurgical waste leachates. First, model solutions were prepared to describe the properties of MMt, sorption kinetic and isotherm models. The determined elimination efficiency was higher than 98 %. The qmax values were – in model solutions – determined to be 34.3, 2.84 and 7.25 mg/g for Zn(II), Cd(II) and Pb(II), respectively. Then, the MMt was applied in order to eliminate of Zn(II), Cd(II) and Pb(II) ions from actual metallurgical waste leachates. The experimental data obtained from the metallurgical waste leachates corresponded with the data obtained from the model solutions. The equilibrium metal uptake capacities obtained by heavy metals adsorption from model solution and metallurgical waste leachates followed the order: Zn(II) > Pb(II) > Cd(II) for dust leachates and Zn(II) > Cd(II) > Pb(II) for converter sludge leachates, which directly corresponds with the heavy metal ions concentration in the leachates. Moreover, the elimination of Zn(II), Cd(II) and Pb(II) by MMt was higher than 98 % even in the fifth recycling experiment cycle. After the sorption, the sorbent was still magnetically active, facilitating its removal from the solution. MMt proved to be an efficient and regenerable sorbent, applicable for wastewater treatment.